Pericardial Mass in an Immunocompetent Young Male – An Elusive Case - Sidhant Sachdeva; Rohit Tandon; Kartik Joshua Sharma; Rajiv Gupta (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Invasive Cardiac aspergilloma involving only the pericardium are extremely rare tumors especially in patient who is not immunocomprised. Multimodality imaging is necessary although definitive diagnosis requires surgical excision because usually these patients require lifelong antifungal therapy.